Proposed Criteria for the Necessary Conditions for Shamanic Journeying Imagery - ROCK, ADAM J.; KRIPPNER, STANLEY (Journal of Scientific Exploration, 2010)
Despite renewed interest in shamanic patterns of phenomenal properties such as journeying imagery, these phenomena are neither well defined nor sufficiently understood. Consequently, we propose criteria pertaining to four necessary conditions for a visual mental image to qualify as a shamanic journeying image. Finally, we demonstrate how these necessary conditions may be used to extrapolate a scoring system that allows one to empirically test, via falsificationism, a visual mental image’s ostensible shamanic status. Keywords: shamanism—shamanic journeying imagery—necessary conditions